The Role of Administrative Performance in Customer Service in Achieving Satisfaction and Belonging to Commercial Dealers A field study on the grain mills sector in Sudan - Mudwi, Sara Suliman Alawad; Mohamed, Reda Abdelfattah Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2023)
This research aims to know the role of administrative performance in customer service in achieving satisfaction and belonging to commercial dealers in the grain mills sector in Sudan, studying the situation in the facility and identifying the obstacles facing the grain sector, The study was based on the assumption that there is a statistically significant relationship between the dimensions of customer service (tangibility, security and empathy) and customer satisfaction. The descriptive analytical approach has been relied upon to address the research problem and test hypotheses. The historical method was also relied upon to follow up on the emergence and development of the company under study. The questionnaire tool was used to collect primary data, Designing two questionnaires aimed at measuring the opinion of the competent departments on the subject of the study and distributing them to each of the employees of the Siva Grain Mill and to the mill’s customers, Where the sample size reached 200 individuals, the study reached a number of results, the most important of which are, There is a statistically significant relationship between customer service dimensions and customer satisfaction (tangibility, safety, empathy), The results of the study also showed a direct, moral and positive impact of customer service management in attracting the customer, gaining his trust and increasing his loyalty to the organization and its products. And that the customer feels confident by 96%, and the study confirmed that there is a feeling of security for customers in dealing with the company by 96%, and that the workers enjoy human feelings and tact by 75.3%.. The study recommended the need to re-maintain plans, programs, objectives, laws and regulations in line with the stage of customer service management implementation.
Keywords: Customer Service; Customer Satisfaction; Sudan Grain Mills